INsPECT, an open-source and versatile software for automated quantification of (Leishmania) intracellular parasites - Yazdanparast, Ehsan (2018)
Intracellular protozoan parasites are causative agents of infectious diseases that constitute major health problems for developing countries. Leishmania sp., Trypanosoma cruzi or Toxoplasma gondii are all obligate intracellular protozoan parasites that reside and multiply within the host cells of mammals, including humans. Following up intracellular parasite proliferation is therefore an essential and a quotidian task for many laboratories working on primary screening of new natural and synthetic drugs, analyzing drug susceptibility or comparing virulence properties of natural and genetically modified strains. Nevertheless, laborious manual microscopic counting of intracellular parasites is still the most commonly used approach. Here, we present INsPECT (Intracellular ParasitE CounTer), an open-source and platform independent software dedicated to automate infection level measurement based on fluorescent DNA staining. It offers the possibility to choose between different types of analyses (fluorescent DNA acquisitions only or in combination with phase contrast image set to further separate intra-from extracellular parasites), and software running modes (automatic or custom). A proof-of-concept study with intracellular Leishmania infantum parasites stained with DAPI (49,6-diamidino-2-phenylindole) confirms a good correspondence between digital results and the "gold standard" microscopic counting method with Giemsa. Interestingly, this software is versatile enough to accurately detect intracellular T. gondii parasites on images acquired with High Content Screening (HCS) systems. In conclusion, INsPECT software is proposed as a new fast and simple alternative to the classical intracellular Leishmania quantification methods and can be adapted for mid to large-scale drug screening against different intracellular parasites.